Spermatological characters of the pseudophyllidean cestode Bothriocephalus scorpii (Müller, 1776) - Levron, Céline; Brunanská, Magdaléna; Poddubnaya, Larisa G (Parasitology international, 2006)
Spermiogenesis of Bothriocephalus scorpii (Cestoda, Pseudophyllidea) includes an orthogonal development of two flagella, followed by a flagellar rotation and a proximo-distal fusion with the median cytoplasmic process. The fusion occurs at the level of four attachment zones. The presence of dense material in the apical region of the differentiation zone in the early stage of spermiogenesis appears to be a characteristic feature for the Pseudophyllidea. The mature spermatozoon possesses two axonemes of 9+"1" pattern of the Trepaxonemata, nucleus, cortical microtubules, electron-dense granules and crested body. The anterior part of the gamete exhibits a centriole surrounded by electron-dense tubular structures arranged as incomplete spiral. When the crested body disappears, the electron-dense tubular structures are arranged into a ring encircling the axoneme. The electron-dense tubular structures and their arrangement appear to be a specific feature for the clade "Bothriocephalidea". The organization of the posterior extremity of the gamete with the nucleus is described for the first time in the Pseudophyllidea.
Keywords: buněčné jádro; Flagella; Microtubules; mužské pohlaví; transmisní elektronová mikroskopie; flagella; mikrotubuly; Cell Nucleus; zvířata; Spermatogenesis; Microscopy, Electron, Transmission; Cestoda; centrioly; Spermatozoa; spermatogeneze; Centrioles; spermie; Male; Animals